PERANCANGAN SISTEM INFORMASI BOOKING PEREKAMAN E-KTP (SI MBOK) BERBASIS WEB - Basri, Hasan; Alfarizi, Salman; Mulyawan, Alif Rizqi; Wiguna, Aldi; Habiba, Izmi (LPPM Universitas Nusa Mandiri, 2019)
A based information system is a system that can be used for the dissemination of information through internet services. In this case, the internet is becoming the provider of a set of information that is posted or uploaded, so that the public can see it every time. Therefore the presence of the internet makes it easier for people to be able to implement the results of the analysis of a system so that the formation of web-based information systems. Government services were supposed to use web-based information systems, it is used in order to obtain maximum work achievement. As an example, a case study a Government Ministry was having some complaints from the community is a service of recording E-ID CARD that is experiencing such a long queue. Therefore this web-based information systems within the scope of the reservation Recording E-ID CARD can reduce prolonged queue numbers so that people feel not satisfied against the Government. On this research produced a design of web-based information systems that can be implemented on the Booking process of recording E-ID CARDS in each Government Ministry offices.